Strategi Pragmatik dalam Penciptaan Humor di Televisi - Riris Tiani (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
Humors  function  not only just entertain, but also has educated function viewer to think creative. This study aims to determine the pragmatic strategy in the creation of humor that aired on some Indonesian television. The research domain uses the assessment of the humorous theory of Asa Berger. The unit of analysis of this research are words, phrases, and sentences as verbal markers of speech humor. The results of research include misunderstanding techniques with idiom meaning of a word that raises a different meaning; The technique of deceiving by asking a question and a sentence indirectly outwits the other person, so the humorist looks smarter than his opponent; Mocking technique by directly criticizing the speaker because his speech sounds weird; And sound-playing techniques by replacing a phoneme in a word which then creates a different meaning.